EDUKASI TEKNOLOGI INFORMASI DALAM KONSEP SMART VILLAGE DI DESA SEI LEMBU MAKMUR KABUPATEN KAMPAR - Sukri Sukri; May Valzon; Salamun Salamun; Muhammad Yazid; Kenepri Kenepri; Siti Juariah (Jurnal Pengabdian Masyarakat Multidisiplin, 2022)
The village area is a location far from the city which has many shortcomings, especially information technology communication. The best development and the fastest and most efficient way of developing information communication is to build from the bottom up at the village level. Every village in Indonesia must be independent and be able to develop themselves to obtain and share information. For this reason, the government has begun to implement a system of development and development from the outskirts or the lowest level, which is called the village and then to the urban area. To support this development, the government created the Smart Village information technology concept. The Smart Village concept has an agenda to strengthen rural management through the use of information and communication technology. In this regard, the Government continues to innovate and be creative to support the Smart Village program. Sei Lembu Makmur Village, Kampar Regency, Riau Province is a village located approximately 45 kilometers from the provincial capital. For this reason, information technology education and data communication through Smart Villages are needed so that village governments can develop Smart Villages independently and community leaders and agencies in the local village area can accept Smart Village development directly in the village.